Analisis Makna Lebaran Ketupat di Kabupaten Grobogan Jawa Tengah - Anisa Alfisyah; Natasya Java Zeiza Shaputri; Regita Cahya Widadari; Melina Lestari (Asosiasi Asesmen Pendidikan (AAP), 2026)
This research aims to analyze the meaning of Ketupat Eid in Grobogan Regency, Central Java. This research uses a qualitative approach with narrative methods. Researchers conducted interviews with two community leaders in Grobogan Regency, Central Java. Data analysis uses Miles Huberman with stages of data collection, organizing data, reading data, coding, developing categorization, interpreting data, verifying findings, and presenting findings. The results of this research are that Eid Ketupat has deep social and religious meaning. Apart from being a form of gratitude after completing the Shawwal fast, this celebration also strengthens social and family ties. This event is often accompanied by friendly activities, visiting each other with family and neighbors, and sharing typical foods such as ketupat, opor ayam, and fried chili sauce. Overall, Eid Ketupat is not only an extension of the Eid al-Fitr celebration, but also an opportunity to strengthen social ties and revive local traditions that have been passed down from generation to generation.